Ética y moral en los discursos académicos selectos de Mons. Leonidas Proaño. - Mendoza Vargas, Jonathan Dennys (2024)
The present research determines the patterns of ethical and moral relations present in the discourses of Mg. Leonidas Proaño under the analysis of the structuralist narrative proposed by Roland Barthes. By means of this qualitative approach of a basic type, under a bibliographic study design, a compilation text of speeches by Monsignor Leonidas Proaño, called "Words of Liberation", is worked on, specifically in six speeches selected in a selection sample according to ethics and morals in the social struggle of the peoples. To this end, a table of discursive decomposition into functions is applied that responds to the analysis of the stories of Roland Barthes (1977), establishing relationships to an existentialist social fact present in the discourses with a humanist sense in favor of the vulnerable social classes. Thus, within the results, different indications are obtained that maintain and verify ethical-moral relations that characterize the discourses and consequently Proaño. Likewise, it is concluded in a general way that the discourses of Proaño are implicitly presented, therefore, the virtues found in Proaño, summarize the very meaning of man and of language itself. In short, thoughts in discourses like language are philosophical facts that defend the history and existence of man. Ethics and morality for Proaño are not asked for or governed by martyrdom or compassion, but are a way of being, that is, they are consequent to the existence of one's own being.